Biochemical characterization of the maize cytokinin dehydrogenase family and cytokinin profiling in developing maize plantlets in relation to the expression of cytokinin dehydrogenase genes - Zalabák, David; Galuszka, Petr; Mrízová, Katarina; Podlešáková, Kateřina; Gu, Riliang; Frébortová, Jitka (Plant physiology and biochemistry, 2014)
The cytokinin dehydrogenases (CKX; EC 1.5.99.12) are a protein family that maintains the endogenous levels of cytokinins in plants by catalyzing their oxidative degradation. The CKX family in maize (Zea mays L.) has thirteen members, only two of which--ZmCKX1 and ZmCKX10--have previously been characterized in detail. In this study, nine further maize CKX isoforms were heterologously expressed in Escherichia coli, purified by affinity and ion-exchange chromatography and biochemically characterized. ZmCKX6 and ZmCKX9 could only be expressed successfully after the removal of putative sequence-specific vacuolar sorting signals (LLPT and LPTS, respectively), suggesting that these proteins are localized to the vacuole. Substrate specificity analyses revealed that the CKX isoforms can be grouped into two subfamilies: members of the first strongly prefer cytokinin free bases while members of the second degrade a broad range of substrates. The most active isoform was found to be ZmCKX1. One of the studied isoforms, ZmCKX6, seemed to encode a nonfunctional enzyme due to a mutation in a conserved HFG protein domain at the C-terminus. Site-directed mutagenesis experiments revealed that this domain is essential for CKX activity. The roles of the maize CKX enzymes in the development of maize seedlings during the two weeks immediately after radicle emergence were also investigated. It appears that ZmCKX1 is a key regulator of active cytokinin levels in developing maize roots. However, the expression of individual CKX isoforms in the shoots varied and none of them seemed to have strong effects on the cytokinin pool.
Keywords: Cytokinins; Molecular Sequence Data; cytokininy; elektroforéza v polyakrylamidovém gelu; ZmCKX; IPT; cZRMP; cis-zeatin; N(6)-(Δ(2)-isopentenyl)adenine; sekvence aminokyselin; regulace genové exprese enzymů; DMAPP; Gene Expression Regulation, Plant; trans-zeatin riboside-5′-monophosphate; chromatografie iontoměničová; Escherichia coli IMPACT expression system; substrátová specifita; cytokinin dehydrogenase; kukuřice setá; AtCKX; cis-zeatin-N9-glucoside; isopentenyl transferase; Zea mays L.; cZ; DNA primery; Mutagenesis, Site-Directed; iPR; trans-zeatin; trans-zeatin riboside; dimethylallyl diphosphate; tZRMP; Cytokinin dehydrogenase; N(6)-(Δ(2)-isopentenyl)adenosine-5′-monophosphate; polymerázová řetězová reakce s reverzní transkripcí; 2,6-dichlorophenolindophenol; DHZ; Base Sequence; sekvence nukleotidů; chromatografie afinitní; mutageneze cílená; Electrophoresis, Polyacrylamide Gel; EDTA; N(6)-(Δ(2)-isopentenyl)adenine-N9-glucoside; Zea mays; CKX; cZ9G; dihydrozeatin; ethylenediaminetetraacetic acid; trans-zeatin-N9-glucoside; tZ; Amino Acid Sequence; Oxidoreductases; fylogeneze; cis-zeatin riboside-5′-monophosphate; iP9G; regulace genové exprese u rostlin; Gene Expression Regulation, Enzymologic; tZ9G; Cytokinin; Substrate Specificity; Reverse Transcriptase Polymerase Chain Reaction; DCPIP; tZR; molekulární sekvence - údaje; Substrate preference; iPRMP; N(6)-(Δ(2)-isopentenyl)adenosine; DNA Primers; Chromatography, Affinity; Phylogeny; cytokinin dehydrogenase from Arabidopsis thaliana; iP; Chromatography, Ion Exchange; cytokinin dehydrogenase from Zea mays; oxidoreduktasy